2006
DOI: 10.1139/a05-016
|View full text |Cite
|
Sign up to set email alerts
|

Sediment delivery in managed forests: a review

Abstract: The opening or removal of forest canopies during harvesting or land clearing results in a predictable sequence of responses, the descriptions of which appear remarkably similar around the world. Such activities are now widely acknowledged to have adverse impacts upon water quality and in-stream ecology. Sediment delivery, therefore, encapsulates the dominant process by which water resources are impacted and the process that can be best managed to limit off-site impacts. This paper is a review of current proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
117
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(121 citation statements)
references
References 77 publications
4
117
0
Order By: Relevance
“…These were the sum of the average proportion of grid cells used for forestry, intensive animal and plant production (that is, land use) which were used as a surrogate for sedimentation (Trimble and Mendel, 1995;Croke and Hairsine, 2006). The average difference in altitude over each upstream grid cell (that is, slope) was used as a surrogate for the frequency of deep slow-flowing pools.…”
Section: Landscape Geneticsmentioning
confidence: 99%
“…These were the sum of the average proportion of grid cells used for forestry, intensive animal and plant production (that is, land use) which were used as a surrogate for sedimentation (Trimble and Mendel, 1995;Croke and Hairsine, 2006). The average difference in altitude over each upstream grid cell (that is, slope) was used as a surrogate for the frequency of deep slow-flowing pools.…”
Section: Landscape Geneticsmentioning
confidence: 99%
“…However, forest roads have been associated with environmental problems in many timber producing regions [3]. Soil erosion and potential for sediment contributions to streams are common concerns associated with poorly designed, constructed, or maintained forest roads [4][5][6].…”
Section: Forest Roads Erosion and Sedimentmentioning
confidence: 99%
“…While previous research clearly supports the premise that forest roads and stream crossings with inadequate or poorly implemented BMPs can accelerate soil erosion and, potentially, sedimentation, numerous research reviews have concluded that BMPs [4,7,[45][46][47], minimum standard roads [48] low-impact harvesting [49], reduced-impact logging [50], or similar techniques can be used to reduce soil erosion and sedimentation. Following the passage of the Federal Water Pollution Control Act of 1972, state forestry agencies developed Forestry BMPs [45,46] specifically designed to minimize the erosion and sediment associated with forest operations with major emphases on forest roads, skid trails, and stream crossings [7,[45][46][47]51,52].…”
Section: Forestry Bmps and Roadsmentioning
confidence: 99%
“…Canada has the 3rd highest freshwater supply in the world; 55% of this runoff is generated in boreal drainage regions, which is proportionate to area (Statistics Canada 2010). Despite their abundance, these water resources are fragile and under threat from pollution, climate change, invasive species, and changes in land use (Schindler 2001;Croke and Hairsine 2006;Monteith et al 2006;Kreutzweiser et al 2008Kreutzweiser et al , 2013Schindler and Lee 2010;Webster et al, Manuscript in preparation;Langor et al, Manuscript in preparation).…”
Section: Select Notable Features Of the Boreal Zonementioning
confidence: 99%